Association between BNT162b2 or CoronaVac COVID-19 vaccines and major adverse cardiovascular events among individuals with cardiovascular disease. Issue 10 (22nd June 2022) - Ye, Xuxiao; Ma, Tiantian; Blais, Joseph E; Yan, Vincent K C; Kang, Wei; Chui, Celine S L; Lai, Francisco T T; Li, Xue; Wan, Eric Y F; Wong, Carlos K H; Tse, Hung Fat; Siu, Chung Wah; et al.
Abstract: Aims: Concern about the cardiovascular safety of coronavirus disease 2019 (COVID-19) vaccines among individuals with cardiovascular disease (CVD) may lead to vaccine hesitancy. We sought to assess the association between two COVID-19 vaccines, BNT162b2 and CoronaVac, and the risk of major adverse cardiovascular events (MACE) in individuals with established CVD. Methods and results: We identified individuals with a history of CVD before 23 February 2021 and a diagnosis of MACE between 23 February 2021 and 31 January 2022 in Hong Kong. MACE was defined as a composite of myocardial infarction, stroke, revascularization, and cardiovascular death. Electronic health records from the Hong Kong Hospital Authority were linked to vaccination records from the Department of Health. A self-controlled case-series method was used to evaluate the risk of MACE for 0–13 and 14–27 days after two doses of COVID-19 vaccine. We estimated incidence rate ratios (IRRs) to compare the risk of MACE between each risk period and the baseline period. A total of 229 235 individuals with CVD were identified, of which 1764 were vaccinated and had a diagnosis of MACE during the observation period (BNT162b2 = 662; CoronaVac = 1102). For BNT162b2, IRRs were 0.48 [95% confidence interval (CI) 0.23–1.02] for the first dose and 0.87 (95% CI 0.50–1.52) for the second dose during the 0–13 days risk period, 0.40 (95% CI 0.18–0.93) for the first dose and 1.13 (95% CI 0.70–1.84) for the second dose during the 14–27 days risk period. For CoronaVac, the IRRs were 0.43 (95% CI 0.24–0.75) for the first dose and, 0.73 (95% CI 0.46–1.16) for the second dose during the 0–13 days risk period, 0.54 (95% CI 0.33–0.90) for the first dose and 0.83 (95% CI 0.54–1.29) for the second dose during the 14–27 days risk period. Consistent results were found in subgroup analyses for different sexes, age groups and different underlying cardiovascular conditions. Conclusion: Our findings showed no evidence of an increased risk of MACE after vaccination with BNT162b2 or CoronaVac in patients with CVD. Future research is required to monitor the risk after the third dose of each vaccine. Graphical Abstract: Graphical Abstract There was no evidence of an increased risk of major adverse cardiovascular events after vaccination with BNT162b2 or CoronaVac in patients with cardiovascular disease.